The AGN content of deep radio surveys and radio emission in radio-quiet AGN. Why every astronomer should care about deep radio fields. Issue Volume 9:Issue S304(2013) (25th July 2014) - Padovani, P.; Bonzini, M.; Miller, N.; Kellermann, K. I.; Mainieri, V.; Rosati, P.; Tozzi, P.; Vattakunnel, S.
Abstract: We present our very recent results on the sub-mJy radio source populations at 1.4 GHz based on the Extended Chandra Deep Field South VLA survey, which reaches ~ 30 μJy, with details on their number counts, evolution, and luminosity functions. The sub-mJy radio sky turns out to be a complex mix of star-forming galaxies and radio-quiet AGN evolving at a similar, strong rate and declining radio-loud AGN. While the well-known flattening of the radio number counts below 1 mJy is mostly due to star-forming galaxies, these sources and AGN make up an approximately equal fraction of the sub-mJy sky. Our results shed also light on a fifty-year-old issue, namely radio emission from radio-quiet AGN, and suggest that it is closely related to star formation, at least at z ~ 1.5 − 2. The implications of our findings for future, deeper radio surveys, including those with the Square Kilometre Array, are also discussed. One of the main messages, especially to non-radio astronomers, is that radio surveys are reaching such faint limits that, while previously they were mainly useful for radio quasars and radio galaxies, they are now detecting mostly star-forming galaxies and radio-quiet AGN, i.e., the bulk of the extragalactic sources studied in the infrared, optical, and X-ray bands.